Operation of research ethics committees in Colombia, Costa Rica, Guatemala, and Mexico: Mesoamerican Project - Angélica Ángeles-Llerenas; James F. Thrasher; Rosalinda Domínguez-Esponda; Ruy López-Ridaura; Ruth Macklin (Instituto Nacional de Salud Pública, 2021)
Objective. To attain a better understanding of the structure and processes of Research Ethics Committees (REC) in the low-and middle-income countries of the Mesoamerican region. The objectives are knowing the operational practices of the RECs regarding project evaluation, training needs, and infrastructure. Materials and methods. The REC training and needs assessment involved an online survey of all the RECs (n=55) identified in Colombia (n=11), Costa Rica (n=5), Guatemala (n=5), and Mexico (n=34). Results. Participants reported inadequate infrastructure for its proper operation (only 49.1 %, or 27/55, have an exclusive office to safeguard files); insufficient administrative staff (47.3%, 26/55), or financial resources to conduct active site monitoring (85.6%, 47/55) to ensure the protection of rights and welfare of study participants. Conclusions. Investments in REC member training and infrastructure are needed to ensure compliance of REC evaluations with the standards for ethical conduct of research.